Implementation of Green Accounting for MSMEs in and Outside the Mining Areas Palu City - Ramadhan, Sahrul; Usman, Rudy; Indrisari, Rahayu; Betty, Betty (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the implementation of green accounting in MSMEs operating in the Poboya mining area and outside the mining area in Palu City. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews with six MSME informants from various business types. The results showed striking differences in environmental awareness, waste management, and readiness to implement green accounting. MSMEs in the mining area have a reactive environmental awareness due to exposure to the impacts of pollution, while MSMEs outside the mining area have a normative awareness driven by social values and business image. Waste management practices in MSMEs within the mining area emphasize pollution mitigation, while MSMEs outside the mining area focus on efficient use of materials. The study also found that all MSMEs have not implemented formal environmental cost recording due to limited knowledge and the absence of simple guidelines for green accounting. Nevertheless, all informants stated that the implementation of green accounting is important for business sustainability and environmental preservation. These findings emphasize the need for education, mentoring, and a simple recording model tailored to the capacity of MSMEs to support the implementation of green accounting in the future.